Make: getting started with soldering : a hands-on guide to making electrical and mechanical connections - De Vinck, Marc (Maker Media, 2017)
Getting Started with Soldering not only teaches new makers and experimenters the core principles of soldering, it also functions as an excellent reference and resource for beginners and more advanced makers alike. The book guides readers through the fundamentals of soldering, explains the tools and materials, demonstrates proper techniques, and shows how to fix mistakes or broken connections. It even includes guidance on more advanced techniques such as surface-mount soldering for electronics. From choosing the right soldering iron to making perfect connections, readers will acquire the knowledge and skills needed to form a strong foundation for a lifetime of making. Soldering is a core concept in making, electronics prototyping, and home repairs The many different types of soldering -- requiring different materials and tools -- are explained with easy-to-follow instructions Full-color photographs and illustrations throughout create a visually engaging format for learning Pricing and technical considerations help readers select the best tools for their budgets and needs Troubleshooting guidelines show how to repair solder connections that have failed from improper technique or from age.